Soil microbiota enhance the population growth rate of a nitrogen-fixing herbaceous legume - Ramula, Satu; Blande, James D.; Kalske, Aino (Oxford University Press (OUP), 2025)
Soil microbiota can modify a plant's growth and chemistry, with consequences for plant population persistence. Therefore, an approach that considers the entire life cycle of a given plant species may be necessary for quantifying the net effect of soil microbiota on longer-lived plants. Here, we investigated the effects of soil microbiota on the fitness-related traits and population growth rate of the nitrogen-fixing legume Lupinus polyphyllus. Using seeds collected from native (North American) and invasive (Finnish) populations of the species, we conducted a greenhouse experiment in which we manipulated the soil microbiota by adding to plants either intact or autoclaved soil inoculum obtained from invasive populations. We grew the plants for two growing seasons and recorded six fitness-related traits (height early and later in life, survival, flowering probability, number of flowering shoots, inflorescence length), characterized floral volatiles, and estimated the asymptotic population growth rate (lambda) using a demographic model. With the intact soil inoculum, flowering probability tended to be higher regardless of plant origin, while for early height, the effect of the inoculum treatment depended on plant origin. The other traits and floral volatile composition were not affected by soil inoculum treatment. At the population level, demographic models confirmed the positive effect of the intact soil inoculum, which yielded 130% and 30% greater lambda for plants of invasive and native origins, respectively, than the autoclaved soil inoculum treatment. These results demonstrate that, at least under greenhouse conditions, soil microbiota contribute to plant population persistence and may affect species abundance. Moreover, our findings indicate that a demographic approach that considers the entire life cycle is needed to assess the net effect of soil microbiota on plant populations.